THE EFFECTIVENESS OF DISCOVERY AND PROBLEM SOLVING IN IMPROVING THE PROBLEM SOLVING SKILLS IN MATHEMATICS - Yosse Dwi Saputro; Indri Anugraheni (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2020)
This research aims to find out the effectivenes of Discovery Learning and Problem Solving models in learning mathematics on the fourth grade students of elementary school in terms of problem solving skills. The samples was elementary school in a cluster of garuda in kabupaten Jepara. The sample was taken use observations and tests. The samples consisted of 2 elementary school with 65 students. The research method was experimental design used static-group comparison. The instruments used to measure the students problem solving skills were rubric and problem solving test. The data analysis techniques was t test and descriptive. The results obtained from the experimental class by the number of students (N) with 35 students with the average score of 77.79, meanwhile the control class obtained the average score of (n) 72.91 with 30 students. The test result obtained t coefficient of t count of the sig 0.368 (2 tailed) 0.021. Because the value was <0,05, H0 was rejected and Ha was accepted that meant that there were significant differences in the implementation of the discovery learning model and problem solving modelin improving problem solving skills of grade 4 students of the elementary school on learning mathematics.